Chemoenzymatic stereoconvergent synthesis of 3-O-benzoyl azidosphingosine - Compostella, F; Franchini, F; Giovenzana, G. B; Panza, L; PROSPERI, DAVIDE; Ronchetti, F. (Tetrahedron: Asymmetry, 2002)
The synthesis of 3-O-benzoyl azidosphingosine 1 through a stereoconvergent approach is described. Nucleophilic addition of the Grignard reagent of 1-pentadecyne to cyclohexylidene-D-glyceraldehyde results in a mixture of diastereoisomeric propargylic alcohols. Subsequent enzymatic separation of these diastereoisomers, mediated by lipase from Candida antarctica, Mitsunobu inversion on the wrong diastereoisomer and extremely efficient introduction of azide using a chloromesylate leaving group affords the title compound in 30% overall yield